STUDENTS’ PERCEPTION TOWARD TIKTOK MEDIA TO IMPROVE THEIR SPEAKING ABILITY - Isty Manggo; Nihta Liando; Trully Wungow (Program Studi Pendidikan Bahasa Inggris, 2022)
The COVID-19 pandemic has had a significant impact on all sectors of life, including education. The Minister of Education and Culture has established a policy relating to online teaching and learning in order to prevent rising instances. In carrying out online learning, the right learning media is needed, so that learning can continue to run well. The purpose of this study is to ascertain how students feel about using TikTok as a teaching tool. With the aid of a questionnaire as a research instrument, this study employs a quantitative descriptive analytic technique. There were samples in this investigation, and there were 18 grade VIII students of SMP Negeri 14 Dumoga who had participated in the Covid-19 pandemic's use of TikTok as a teaching tool. The results showed that the eighth-grade students of SMP Negeri 14 Dumoga liked the use of Tiktok as a medium for learning English, especially speaking. The use of TikTok as a learning medium is quite good for use in the process of learning English, especially in students' speaking. This can be shown in the results of data that has been processed and calculated based on predetermined criteria. Therefore, it is hoped that Tiktok can be a reference for learning media to learn English, especially speaking.